The stock market - Dice, Charles Amos; Eiteman, Wilford J.; Eiteman, David K. (New York : McGraw-Hill, 1966)
The first edition explained in simple, straight forward language how the stock market was organized and how it operated. Automation has introduced many innovations in trading procedures. The fourth edition covers all the new developments.
In the earlier editions Dice's name appeared first on the title page.
Bibliographical footnotes.
osc 13/07/2018
Loans
Keywords: Stock exchanges; Speculation; Stocks